Preliminary review of the geotechnical characteristics and shear strength estimates of small scale anisotropic waveform formations of the Pilbara, Western Australia - Tokimoto, S; Mercer, KG (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Anisotropic rock masses such as the Hamersley Group found within the Pilbara region of Western Australia commonly exhibit pervasive folding in wavelengths ranging from several centimetres to large regional folding with wavelengths of up to several kilometres. All folding influences the stability of open pit slopes however the influence of relatively small scale folding is particularly difficult to account for in limit equilibrium slope stability analysis. In addition, existing research work on assessing the shear strength of anisotropic rock masses has thus far, only considered the effect of planar discontinuities. Using data from published literature, the paper will provide a general over view of the geological and geotechnical characteristics of formations within the Pilbara region of Western Australia where waveform formations are typically found. The paper will then go on to review the scale at which the waveform folding of bedding is likely to have the greatest impact on the shear strength of anisotropic rock masses and how these different scales can be modelled when assessing the stability of pit slopes. Finally the paper will present some preliminary results of numerical modelling studies of the shear strength characteristics of small scale waveform formations using two commonly occurring rock types found in the Pilbara region.